Numerical solution and validation concerning a descriptive model of a simultaneous heat and mass transfer process - Villa Saravia, Luis Tadeo (2011)
This paper deals with the numerical solution of an initial moving boundary problem (IMBVP) arising from a simplified version of a free boundary problem (IFBVP) which was formulated in another paper, as a mathematical model of heat and moisture transfer during the bubbling stage of an immersion frying process of stick shaped natural potato. The IMBVP was solved numerically using an explicit finite difference method, immobilizing the moving boundary through the use of the well known Landau transformation. The simulation output provides the temperature and moisture profiles and the amount of free moisture lost by vaporization. The model was validated by comparing the predicted results with experimental data. A good agreement was obtained.